Endogenous Annexin-A1 Regulates Haematopoietic Stem Cell Mobilisation and Inflammatory Response Post Myocardial Infarction in Mice In Vivo. Issue 1 (December 2017) - Qin, Cheng; Finlayson, Siobhan; Al-Sharea, Annas; Tate, Mitchel; Blasio, Miles; Deo, Minh; Rosli, Sarah; Prakoso, Darnel; Thomas, Colleen; Kiriazis, Helen; Gould, Eleanor; Yang, Yuan; et al.
Abstract Endogenous anti-inflammatory annexin-A1 (ANX-A1) plays an important role in preserving left ventricular (LV) viability and function after ischaemic insultsin vitro, but its long-term cardioprotective actionsin vivo are largely unknown. We tested the hypothesis that ANX- A1-deficiency exaggerates inflammation, haematopoietic stem progenitor cell (HSPC) activity and LV remodelling in response to myocardial ischaemiain vivo . AdultANX - A1 −/− mice subjected to coronary artery occlusion exhibited increased infarct size and LV macrophage content after 24–48 h reperfusion compared with wildtype (WT) counterparts. In addition, ANX - A1 −/− mice exhibited greater expansion of HSPCs and altered pattern of HSPC mobilisation 8 days post-myocardial infarction, with increased circulating neutrophils and platelets, consistent with increased cardiac inflammation as a result of increased myeloid invading injured myocardium in response to MI. Furthermore, ANX - A1 −/− mice exhibited significantly increased expression of LV pro-inflammatory and pro-fibrotic genes and collagen deposition after MI compared to WT counterparts. ANX-A1-deficiency increased cardiac necrosis, inflammation, hypertrophy and fibrosis following MI, accompanied by exaggerated HSPC activity and impaired macrophage phenotype. These findings suggest that endogenous ANX- A1 regulates mobilisation and differentiation of HSPCs. Limiting excessive monocyte/neutrophil production may limit LV damagein vivo . Our findings support further development of novel ANX-A1-based therapies to improve cardiac outcomes after MI.